Development and Characterization of Embryonic Stemlike Cell Culture from Carassius auratas (Linnaeus, 1758) - Kumar, Abhay; Kanyal, Pooja; Bedekar, Megha K.; Kumar, A. Pavan; Sushila, N.; Tripathi, Gayatri (Fishery Technology, 2017)
Embryonic stem cells are pluripotent cells, capable of differentiating into various cell types. In the present study, feeder cell-free culture of midblastula embryos of the Goldfish (Carassius auratus) was carried out. Embryonic stem cells were derived from mid-blastula stage embryos using pronase to release the inner cell mass (ICM). The cells were cultured in Leibovitz-15 medium on gelatin-coated cell culture well plates supplemented with 15% fetal bovine serum, 1% goldfish serum, basic fibroblast growth factor and leukaemia inhibitory factors (LIF) and were incubated at 28Â°C. The ES-like cells were characterized by their unique round and polygonal morphology, elevated activity of alkaline phosphatase, spherical three-dimensional embryoid body formation, chromosomal diploid number (2n=50). The expression of Oct4, a member Oct family of POU transcription factors, which play a key role in regulating stem cell pluripotency and differentiation, was used for characterization of undifferentiated pluripotent ES cells. The expression of Oct4 in embryonic stem-like cell (2nd passage) and gonads of goldfish was studied by RT- PCR. Embryonic stem-like cells culture from the mid blastula embryo of C. auratus would be a useful tool for cellular development and differentiation studies.